[tex]\frac{30}{ \sqrt{3} - 3 \sqrt{5} } \\ \\ =\frac{30}{ \sqrt{3} - 3 \sqrt{5} } \times \frac{\sqrt{3} + 3 \sqrt{5}}{\sqrt{3} + 3 \sqrt{5}} \: \\ \\ that \: simply \: means \: multiplying \: by \: 1 \\ \\ \frac{30(\sqrt{3} + 3 \sqrt{5})}{ (\sqrt{3} + 3 \sqrt{5}) (\sqrt{3} - 3 \sqrt{5}) } \: \: \\ \\ by \: using \: formula \: {a}^{2} - {b}^{2} \\ \\ we \: get \\ \\ = \frac{30 \sqrt{3} + 90 \sqrt{5} }{ 3 - 45} \\ \\ = - \frac{30( \sqrt{3} + 3 \sqrt{5}) }{42} \\ \\ = - \frac{10( \sqrt{3} + 3 \sqrt{5}) }{14} \: \: [/tex]